Posthuman bodies - Halberstam, Jack, 1961-; Livingston, Ira, 1956- (Bloomington : Indiana University Press, 1995)
"It is a collection of essays that takes up, in a mostly affirmative way, various challenges to the coherence of the "human body" as a figure through which culture is processed and oriented." Partial contents : The end of the world of White Men ; Class and its close relations : identities among women, servants, and machines ; Soft fictions and intimate documents : can feminism be posthuman? ; Reproducing the posthuman body : ectogenetic fetus, surrogate mother, pregnant man ; The seductive power of science in the making of deviant subjectivity ; Phantom and reel projections lesbians and the (serial) killing-machine ; "Death of the family."
Identity in Oshkosh / Allucquere Rosanne Stone -- Two lessons from Burroughs / Steven Shaviro -- The End of the world of white men / Kathy Acker -- Class and its close relations: identities among women, servants, and machines / Alexandra Chasin -- Soft fictions and intimate documents: can feminism be posthuman? / Paula Rabinowitz -- Reproducing the posthuman body: ectogenetic fetus, surrogate mother, pregnant man / Susan M. Squier -- The Seductive power of science in the making of deviant subjectivity / Jennifer Terry -- Phantom and reel projections: lesbians and the (serial) killing-machine / Camilla Griggers -- 'Death of the family.' or, keeping human beings human / Roddey Reid -- Reading like an alien: posthuman identity in Ridley Scott's Alien and David Cronenberg's Rabid / Kelly Hurley -- Terminating bodies: toward a cyborg history of abortion / Carol Mason -- 'Once they were men, now they're landcrabs': monstrous becomings in evolutionist cinema / Eric White.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Electronic resource, viewed: July 9, 2024.
eBooks on EBSCOhost
Keywords: Bürger, Christa -- 1935-; Human body -- Social aspects; Human body -- Symbolic aspects; Human body (Philosophy); Body image; Sex symbolism; Sex in popular culture; Humanism -- History -- 20th century; Postmodernism; Humanism; Popular culture; Body Image; Humanism; Popular Culture; Corps humain -- Aspect social; Corps humain -- Aspect symbolique; Corps humain (Philosophie); Image du corps; Symbolisme sexuel; Sexualité dans la culture populaire; Humanisme -- Histoire -- 20e siècle.; Postmodernisme; Humanisme; Culture populaire; humanism; popular culture; 42.85 physical anthropology; 17.90 literature in relation with other areas of science and culture; HEALTH & FITNESS -- Beauty & Grooming; Body image; Human body (Philosophy); Human body -- Social aspects; Human body -- Symbolic aspects; Humanism; Postmodernism; Sex in popular culture; Sex symbolism; Kultur; Körper; Kulturwandel; Technischer Fortschritt; Postmoderne; Menselijk lichaam; Seksualiteit; Populaire cultuur; Human body -- Social aspects; Human body -- Symbolic aspects; Human body (Philosophy); Body image; Sex symbolism; Sex in popular culture; Humanism -- History -- 20th century; Postmodernism; 1900-1999; Electronic books; History